2016
DOI: 10.3310/hta20720
|View full text |Cite
|
Sign up to set email alerts
|

UNderstanding uptake of Immunisations in TravellIng aNd Gypsy communities (UNITING): a qualitative interview study

Abstract: Background: Gypsies, Travellers and Roma (referred to as Travellers) are less likely to access health services, including immunisation. To improve immunisation rates, we need to understand what helps and hinders individuals in these communities in taking up immunisations. Aims: (1) Investigate the barriers to and facilitators of acceptability and uptake of immunisations among six Traveller communities across four UK cities; and (2) identify possible interventions to increase uptake of immunisations in these Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 79 publications
1
57
0
1
Order By: Relevance
“…In qualitative studies, a need for clearer, more transparent, and unbiased information about HPV vaccination [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] was identified by some participants, together with the need for more verbal, interactive communication. 52,55,57,65,69 Additionally, some participants recommended providing information in schools, for instance by organising peer discussion groups with vaccinated girls 53,[55][56][57]61,62,67,69 ; while others preferred social media or communication methods that allow more discretion. [52][53][54]62,69 Concerns about vaccine safety…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In qualitative studies, a need for clearer, more transparent, and unbiased information about HPV vaccination [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] was identified by some participants, together with the need for more verbal, interactive communication. 52,55,57,65,69 Additionally, some participants recommended providing information in schools, for instance by organising peer discussion groups with vaccinated girls 53,[55][56][57]61,62,67,69 ; while others preferred social media or communication methods that allow more discretion. [52][53][54]62,69 Concerns about vaccine safety…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…Qualitative studies reported beliefs that HPV vaccination might encourage promiscuity or earlier sexual debut in young girls 61,[65][66][67]100,101,106,108,119 and that the vaccine could lead to unsafe sexual behaviour and a decrease in the use of condoms and cervical cancer screening. 55,57,63,64,66,67,80,106,108,109,119 Additionally, some participants mentioned that the vaccine is being given to girls when they are too young because they have not started to menstruate, are not yet sexually active or married, 54,57,58,61,100,108 or because they are too "naïve and immature" to give their consent. 98,103 Some also reported that it is not easy to talk about HPV vaccination with girls that are so young.…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…Despite fewer barriers to research participation in terms of literacy and language, it was not possible to recruit to the target sample of Showpeople. Some Showpeople expressed reservations about participating in a study which viewed their needs in relation to immunization as separate from the majority population (Jackson et al, 2016).…”
Section: Rewarding Participationmentioning
confidence: 99%
“…Sometimes it pays not to make assumptions about what is driving pockets of poor vaccination, but to focus instead on helping stretched parents who may Year MMR (first dose) coverage WHO target (95%) 8 8 -8 9 8 9 -9 0 9 0 -9 1 9 1 -9 2 9 2 -9 3 9 3 -9 4 9 4 -9 5 9 5 -9 6 9 6 -9 7 9 7 -9 8 9 8 -9 9 Sarah Loving, Vaccine Knowledge Project Manager at the Oxford Vaccine Group, cites the example of an orthodox Jewish group, the Charedi, in North London, where a tailoring of the immunisation programme 7 was required to fit the needs of the community and boost vaccine rates. "The community had lower than average coverage rates and had experienced several outbreaks of vaccine-preventable diseases in recent years, but work with the community found this was more to do with access to immunisation services than vaccine refusal or hesitancy," says Ms Loving.…”
Section: Ease Of Access To Immunisation Is Keymentioning
confidence: 99%
“…Similar work has been done to understand and evaluate barriers to vaccine uptake in travelling communities. 8 In this case, several interventions were identified as important to improve the uptake of childhood vaccines, including flexible and diverse systems for booking appointments, recalls and reminders, as well as cultural competence training for health workers, and an improved system of temporary registration at GP practices for those living on the roadside and in unauthorised encampments.…”
Section: Ease Of Access To Immunisation Is Keymentioning
confidence: 99%